2001
DOI: 10.1073/pnas.041622398
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity array analysis of gene expression for the early detection of disseminated breast tumor cells in peripheral blood

Abstract: Early detection is an effective means of reducing cancer mortality. Here, we describe a highly sensitive high-throughput screen that can identify panels of markers for the early detection of solid tumor cells disseminated in peripheral blood. The method is a two-step combination of differential display and high-sensitivity cDNA arrays. In a primary screen, differential display identified 170 candidate marker genes differentially expressed between breast tumor cells and normal breast epithelial cells. In a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 32 publications
2
77
0
2
Order By: Relevance
“…Ratios were calculated from the mean value of six real-time PCR measurements obtained from three independent PCR runs with duplicate samples. RPLP0 (Martin et al, 2001) and Cyclophilin E (data not shown) were used as a reference to control for the amount of sample material. GLI1 expression in human keratinocytes leads to GLI2 transcription and GLI1 auto-activation…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ratios were calculated from the mean value of six real-time PCR measurements obtained from three independent PCR runs with duplicate samples. RPLP0 (Martin et al, 2001) and Cyclophilin E (data not shown) were used as a reference to control for the amount of sample material. GLI1 expression in human keratinocytes leads to GLI2 transcription and GLI1 auto-activation…”
Section: Resultsmentioning
confidence: 99%
“…Standard deviation was below 20 per cent between all replicate experiments. Large ribosomal protein P0 (RPLP0) was used as a reference standard for all analyses to control for the amount of sample material (Martin et al, 2001) simultaneous increase in GLI1 mRNA levels. We therefore constructed a HaCaT cell line expressing His-tagged GLI2b in a tetracycline-regulated manner.…”
Section: Gli1 Is a Putative Direct Target Of Gli2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are other studies combining DD with array analysis that have experienced the same lack of sensitivity of arrays. Martin and collaborators (Martin et al, 2001) found that less than 10% (12/170) of the DD-isolated sequences spotted on a membrane gave useful results upon further analysis of additional patient samples. Several studies using PCR-DD and mAs as complementary approaches detected few genes (0-10) by both approaches (Outinen et al, 1998;Wells, 1999;Cirelli and Tononi, 2000;Oetting, 2000;Heilig and Sommer, 2004;Pascal et al, 2005).…”
Section: Methods and Strategymentioning
confidence: 99%
“…cDNA synthesis and qRT-PCR analysis were carried out as described in Eichberger et al (2006). Human large ribosomal protein P0 (RPLP0) was used for normalization of sample material in qRT-PCR analysis (Martin et al, 2001). For primer sequences see Supplementary Table S2.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%